Strengthening Cultural Literacy Through Cirebon Folk Tales Incorporating Religious Moderation Values - Nurhannah Widianti; Agus Nuryatin; Teguh Supriyanto; Rahayu Pristiwati (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractThe limited integration of local cultural values and religious moderation in elementary education has hindered the development of students’ character and their understanding of diversity. Although Indonesia possesses rich cultural heritage embedded in regional folklore, these stories are often underutilized as pedagogical resources for fostering tolerance, mutual respect, and harmonious interfaith relations. This study aims to describe the condition of cultural literacy in elementary schools, identify Cirebon folk tales that contain religious moderation values, and examine the implementation of cultural literacy strengthening. Using a qualitative descriptive design, data were collected through interviews, observations, and documentation, then analyzed through data reduction, presentation, and conclusion drawing. The findings show that cultural literacy is inconsistently introduced in schools, that Cirebon folk tales such as Azan Pitu, Klenteng Jamblang, Babad Cirebon, and Nadran contain strong moderation values, and that the strengthening of cultural literacy is implemented through the P3 framework, the School Literacy Movement, and Pancasila Student Profile activities. These results highlight the importance of utilizing local folklore as a culturally grounded medium for cultivating national commitment, tolerance, non-violence, and cultural accommodation among young learners.Keywords: folklore, cultural literacy, religious moderation. AbstrakIntegrasi nilai-nilai budaya lokal dan moderasi agama yang terbatas dalam pendidikan dasar telah menghambat perkembangan karakter siswa dan pemahaman mereka terhadap keragaman. Meskipun Indonesia memiliki warisan budaya yang kaya yang tertanam dalam folklore regional, cerita-cerita ini seringkali kurang dimanfaatkan sebagai sumber daya pedagogis untuk menumbuhkan toleransi, saling menghormati, dan hubungan antaragama yang harmonis. Penelitian ini bertujuan untuk menggambarkan kondisi literasi budaya di sekolah dasar, mengidentifikasi dongeng-dongeng Cirebon yang mengandung nilai-nilai moderasi agama, dan mengkaji implementasi penguatan literasi budaya. Dengan desain deskriptif kualitatif, data dikumpulkan melalui wawancara, observasi, dan dokumentasi, kemudian dianalisis melalui reduksi data, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa literasi budaya diperkenalkan secara tidak konsisten di sekolah, bahwa dongeng-dongeng Cirebon seperti Azan Pitu, Klenteng Jamblang, Babad Cirebon, dan Nadran mengandung nilai-nilai moderasi yang kuat, serta bahwa penguatan literasi budaya dilaksanakan melalui kerangka kerja P3, Gerakan Literasi Sekolah, dan kegiatan Profil Siswa Pancasila. Hasil ini menyoroti pentingnya memanfaatkan folklore lokal sebagai media yang berakar pada budaya untuk menumbuhkan komitmen nasional, toleransi, non-kekerasan, dan akomodasi budaya di kalangan pelajar muda.Kata kunci: cerita rakyat, literasi budaya, moderasi agama.